(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article describes the effectiveness of various graphics programs using 3D modeling of three-dimensional graphics in developing the design culture and professional skills of students, and also provides an example of vertical modeling of the Apparel platform, one of the hydraulic structures in the AutoCAD graphics program. security.